Jurisdictional Approach in REDD+ Implementation for Carbon Trading Management in Central Borneo - Selvia, Fitriana (Jurnal Ilmu Hukum Tambun Bungai, 2024)
Carbon trading is a promising mechanism to mitigate climate change. Indonesia, with its vast forest resources, has the potential to significantly contribute to global carbon reduction efforts. However, challenges such as deforestation and forest degradation persist, particularly in regions like Central Kalimantan. This study explores the potential of a jurisdictional approach to REDD+ in Central Kalimantan, which focuses on multi-level collaboration, local government involvement, performance-based incentives, and effective monitoring, reporting, and verification (MRV). By empowering local communities and aligning with national and international policies, this approach aims to achieve sustainable forest management and carbon emission reduction. This research delves into the key steps involved in implementing a jurisdictional REDD+ approach, including planning, stakeholder engagement, implementation, monitoring and evaluation, and scalability. It highlights the importance of addressing social and economic factors alongside environmental considerations to ensure the long-term success of REDD+ initiatives. By adopting a jurisdictional approach and addressing the complex interplay between environmental, social, and economic factors, Central Kalimantan can position itself as a leader in sustainable forest management and contribute significantly to global climate change mitigation efforts.